I wonder why snakes shed their skin : and other questions about reptiles - O' Niell, Amanda (Danbury, Connecticut : Grolier Inc, 1999)
I Wonder Why Snakes Shed Their Skin is jam-packed with fascinating facts about reptiles, from 'Which reptile has a frightful frill?' to 'Which turtle kicks up a stink?'
Includes index
Keywords: Science